The potential for constructed wetlands to treat alkaline bauxite-residue leachate: phragmites australis growth - Higgins, D.; Curtin, T.; Pawlett, Mark; Courtney, R. (Springer, 2016)
High alkalinity (pH > 12) of bauxite-residue leachates presents challenges for the long-term storage and managements of the residue. Recent evidence has highlighted the potential for constructed wetlands to effectively buffer the alkalinity, but there is limited evidence on the potential for wetland plants to establish and grow in soils inundated with residue leachate. A pot-based trial was conducted to investigate the potential for Phragmites australis to establish and grow in substrate treated with residue leachate over a pH range of 8.6–11.1. The trial ran for 3 months, after which plant growth and biomass were determined. Concentrations of soluble and exchangeable trace elements in the soil substrate and also in the aboveground and belowground biomass were determined. Residue leachate pH did not affect plant biomass or microbial biomass. With the exception of Na, there was no effect on exchangeable trace elements in the substrate; however, increases in soluble metals (As, Cd and Na) were observed with increasing leachate concentration. Furthermore, increases in Al, As and V were observed in belowground biomass and for Cd and Cr in aboveground biomass. Concentrations within the vegetation biomass were less than critical phytotoxic levels. Results demonstrate the ability for P. australis to grow in bauxite-residue leachate-inundated growth media without adverse effects.
Keywords: Hyperalkaline wastes; Macrophytes; Metal removal; Mine water; Passive treatment; Red mud